1996
DOI: 10.1111/j.1445-2197.1996.tb01189.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Aspects of Chronic Low Back Pain

Abstract: Background: Patients with chronic low back pain present physicians with diagnostic and therapeutic problems. Physical treatments tend to have low success rates and it is postulated that this may be because low back pain can be a manifestation of abnormal illness behaviour. Methods: A structured prospective study determined the prevalence of somatization in a sample of 131 adult patients with chronic low back pain using the Illness Behaviour Questionnaire (IBQ) and the Modified Somatic Perception Questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 10 publications
2
26
0
Order By: Relevance
“…The PDI reliably measures self-assessed functional ability in seven areas: occupational, home/family, recreational, social, sexual, activities of daily living, and life support (Gronblad et al, 1993;Tait, Chibnall, & Krause, 1990;Tait, Pollard, Margolis, Duckro, & Krause, 1987). Similar to the MMPI, both are useful for identifying patients whose physical symptom presentations and disability are influenced by non-organic factors (Petrak, Hardt, Kappis, Nickel, & Tiber Egle, 2003;Sikorski, Stampfer, Cole, & Wheatley, 1996). For instance, Brasseux, Greve, Gianoli, Soileau, and Bianchini (2008) found a positive correlation between MSPQ scores and aphysiologic (i.e., non-organic) computerized dynamic posturography sway patterns in a sample of 115 patients with complaints of vestibular dysfunction and hearing impairment.…”
Section: Introductionmentioning
confidence: 93%
“…The PDI reliably measures self-assessed functional ability in seven areas: occupational, home/family, recreational, social, sexual, activities of daily living, and life support (Gronblad et al, 1993;Tait, Chibnall, & Krause, 1990;Tait, Pollard, Margolis, Duckro, & Krause, 1987). Similar to the MMPI, both are useful for identifying patients whose physical symptom presentations and disability are influenced by non-organic factors (Petrak, Hardt, Kappis, Nickel, & Tiber Egle, 2003;Sikorski, Stampfer, Cole, & Wheatley, 1996). For instance, Brasseux, Greve, Gianoli, Soileau, and Bianchini (2008) found a positive correlation between MSPQ scores and aphysiologic (i.e., non-organic) computerized dynamic posturography sway patterns in a sample of 115 patients with complaints of vestibular dysfunction and hearing impairment.…”
Section: Introductionmentioning
confidence: 93%
“…A high percentage of CPPs demonstrate elevated hypochondriasis scores [22] and somatization scores [23] as measured by the Illness Behavior Questionnaire and the Modified Somatic Perceptions Questionnaire, respectively. In addition, when patients with various types of chronic pain are compared with appropriate controls on somatization measures, the CPPs are frequently demonstrated to have greater somatization scores.…”
Section: Under Investigation Yesmentioning
confidence: 99%
“…Von Baeyer et al, 22 Sikorski et al, 24 Ginzburg, 25 Lindal and Uden, 26 Greenough, 13 and Hagg et al 5 concluded that the relationship between pain drawings and the emotional states they tested were too weak to be clinically useful. We have methodologic and statistical concerns with Sivik's 7,15 and Ransford's 1 papers, which leaves little evidence to support pain drawings as predictors of psychologic state.…”
Section: Pain Drawings and Psychologic Statementioning
confidence: 99%